The Role of Sustainable Megamerger Logistics Practices as a Mediator of the Relationship between Human Factors and Company Efficiency: Development of a Theoretical Concept - M. Elfan Kaukab (Journal of Economics, Management, and Business, 2024)
Objective - The purpose of this study is to explore the concept of sustainable megamerger logistics practices and how these variables mediate the influence of human factors on company efficiency interacting with the concept Method - This study was conducted by mapping the theory of socio-ecological interdegradation into a general framework of the conceptual map of the study. Results - This study produces a research proposition, namely that good human factors will encourage regular maintenance, fuel economy, use of eco-driving, smooth acceleration, reduction of idle conditions, efficient route selection, turning off the engine at red lights, use of original oil, and more regular filter changes after the merger so as to encourage the efficiency of the merged company. Implications - This study will contribute to the literature on sustainable supply chains. Originality - This study highlights the importance of internal integration for sustainable megamerger logistics practices and sustainable company efficiency improvements. Second, that environmentally conscious human factors lead to sustainable megamerger logistics practices that improve company efficiency. Third, normative pressures placed on companies can encourage companies to become sustainable. Fourth, sustainable megamerger logistics practices should not ignore inter-organizational and intra-organizational aspects. Fifth, sustainable megamerger logistics practices are essential factors to drive the efficiency of companies that carry out megamergers.